Gödselhantering på ridskolor - Lood, Sara; Odenius, Catharina (2017)
In Sweden, the horse industry is becoming more important to the agriculture and for the society, both in cultural, social and economic ways. The riding school is a large part of today’s society and involves people of all ages. The horses in the riding school produce a large amount of manure that in many cases is transported to landfills. This is a waste of nutrients as well as an environmental problem. The nutrients in horse manure are important resources that should be used as fertilizer on field cultivation. Overfertilization of phosphorus and nitrogen has become an environmental problem and should be considered in the management of the manure management. The horse manure should be seen as a resource but instead it becomes a problem for riding schools. The aim of the study was to investigate how the manure is managed at the Swedish riding schools. The study can serve as a basis for how manure management affects the environment and how a progressive management can lead to economic profitability. The study had two research issues. How will the economy of the riding school be affected by factors in the management of the manure? In which ways can the manure be handled to create environmental sustainability in the long term? The questions of the survey were based on the research issues and emailed to 254 riding schools located in each county in Sweden. Fifty-six riding schools responded, that gives a response rate of 22 %. The majority (75 %) of these riding schools had a plan regarding its manure management and disposal of the manure. Most riding schools answered that the economy affected the manure management but they did not find it difficult to dispose the manure. The conclusion was that a long-term cooperation with nearby farmers were factors as system of disposal, the riding schools location and numbers of horses are taken in account, the manure management can be both environmental sustainable and benefit the riding school economically.